2021
DOI: 10.3389/fphar.2021.664607
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Different Extracts From Triphala Against CCl4-Induced Acute Liver Injury in Mice

Abstract: Background:Triphala is a traditional polyherbal formula used in Indian Ayurvedic and Chinese Tibetan medicine. A wide range of biological activities have been attributed to Triphala, but the impact of various extraction methods on efficacy has not been determined.Purpose: The study aimed to evaluate Triphala extracts obtained by various methods for their hepatoprotective effects and molecular mechanisms in a mouse model of carbon tetrachloride (CCl4)-induced liver injury.Methods: HPLC fingerprinting was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
0
6
0
2
Order By: Relevance
“…It showed that CCP-infected broilers responded but could not successfully increase antioxidant enzymes to scavenge free radicals, causing oxidative damage to the liver and jejunum. Studies have shown that tannins can enhance the mRNA levels of antioxidant enzymes and reduce oxidative stress to protect the health of the body [ 36 , 37 , 38 ]. Consistent with these studies, we found that dietary supplementation with 1000 mg/kg TA could alleviate the up-regulation of Keap1 and Nrf2 mRNA levels and enhance the mRNA levels of GSH-Px1, SOD, CAT in the liver and jejunal CAT in the CCP-challenged broilers, which suggested that dietary supplementation with 1000 mg/kg TA could enhance antioxidant enzyme activities through the activation of the transcription factor Nrf2 downstream of the Nrf2-Keap1 pathway to alleviate oxidative damage in the liver and jejunum caused in the CCP-challenged broilers.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that CCP-infected broilers responded but could not successfully increase antioxidant enzymes to scavenge free radicals, causing oxidative damage to the liver and jejunum. Studies have shown that tannins can enhance the mRNA levels of antioxidant enzymes and reduce oxidative stress to protect the health of the body [ 36 , 37 , 38 ]. Consistent with these studies, we found that dietary supplementation with 1000 mg/kg TA could alleviate the up-regulation of Keap1 and Nrf2 mRNA levels and enhance the mRNA levels of GSH-Px1, SOD, CAT in the liver and jejunal CAT in the CCP-challenged broilers, which suggested that dietary supplementation with 1000 mg/kg TA could enhance antioxidant enzyme activities through the activation of the transcription factor Nrf2 downstream of the Nrf2-Keap1 pathway to alleviate oxidative damage in the liver and jejunum caused in the CCP-challenged broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In the body, CCl 4 can induce metabolic disorders in liver tissue, mainly manifested as mitochondrial dysfunction and lipid peroxide reaction. The dysfunctional mitochondria have high oxidative capacity and produce a large amount of reactive oxygen species, which make the content ratio between reactive oxygen species and protective oxidants unbalanced, resulting in oxidative stress response; the resulting oxidative stress and inflammatory mediator factors further inducing changes in the activity of drug metabolizing enzymes in the liver, the damaged liver tissue presents a series of complex changes in pathological and biochemical characteristics, eventually leading to severe damage to liver function ( Mohi-Ud-Din et al, 2019 ; Wang et al, 2021 ; Wei et al, 2021 ; Sheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ingredients of Avipattikara Churna and Punarnava Mandura have digestive, hepatoprotective, metabolism-enhancing, and antioxidant properties. In this case, improved digestion and metabolism were observed within a few days of initiating the treatment, which probably improved biochemical parameters related to liver functions and lipid metabolism [ [14] , [15] , [16] ]. A daily laxative was also prescribed to ease the expulsion of solid water from the colon.…”
Section: Discussionmentioning
confidence: 99%